The Orthopedic Educator A Pocket Guide (Springer International Publishing, 2018)
This concise pocket guide is the first of its kind to provide a solid foundation for those who are involved in academic orthopedic surgery education for medical students, residents, and faculty and program heads. Opening with an exploration of the history of orthopedic education in the United states as well as a sampling of international experiences, the book then describes curriculum design for competency-based education, teaching as coaching, and how to teach operative skills. A trio of chapters on working with residents covers the sometimes challenging areas of assessment, remediation and providing constructive feedback. Subsequent chapters detail the development of orthopedic faculty and elements of successful programs as well as tips for directors creating or maintaining a program. While several books exist to guide educators in the non-surgical fields, none exist to provide guidance for surgical fields, much less orthopedic surgery. Ideal for any and all professionals involved in orthopedic education, The Orthopedic Educator serves to offer insight for making the most out of the time available for teaching, offering advice from experienced educators on how to build and maintain a successful program.